The clinician–patient working alliance: is it a significant predictor of psychiatric medication adherence in a sample of recently released parolees?. Issue 5 (3rd September 2018) - Calhoun, Stacy
ABSTRACT: Persistent psychiatric symptoms can serve as a major barrier to the successful reintegration of parolees with mental illness. Thus, it is important to identify factors that might impact their mental health recovery, such as low adherence to their treatment regimen. The strength of the clinician/patient working alliance has been found to be significantly associated with psychiatric medication adherence in prior research, but this relationship has not been assessed in a parolee population. Logistic regression analysis was used to determine if patient-rated working alliance was a significant predictor of low psychiatric medication adherence while taking into account alcohol/illegal drug use, age, and ethnicity in a sample of recently released parolees with mental illness ( N = 49). Patient-rated working alliance, age, and ethnicity were not significant predictors of low adherence. Alcohol/illegal drug use during the follow-up period was associated with a significantly increased likelihood of meeting the criteria for low medication adherence (OR = 8.36; 95% CI = 1.60, 43.66). While working alliance was not found to be a significant predictor of medication adherence in this study, further research is needed to examine how substance misuse impacts the clinician–patient working alliance in this population.